El Salvador Financial Sector Assessment Program : Safety Nets and Crisis Management Arrangements - International Monetary Fund (Washington, DC, 2017)
In El Salvador, the banking safety net emergency liquidity assistance, resolution and deposit insurance- faces particular challenges given it operate in the context of official dollarization. The economy was officially dollarized in 2000 with the adoption of the law on financial integration and of the United States (US) dollar as legal tender. Dollarization constrains a central bank's ability to act as a lender of last resort (LOLR) and provide emergency liquidity assistance (ELA). This note discusses the weaknesses of the current framework and recommendations to ensure the safety net functions more effectively and efficiently. To address systemic liquidity risk in the context of official dollarization, the Banco Central de Reservas (BCR) should be provided with more powers and funds to provide emergency liquidity assistance to banks. The bank resolution scheme, which has not been tested, and the deposit insurance fund, which has insufficient funds, both need to be strengthened. Appropriate roles and formal mechanisms to monitor and manage systemic risk and events should be put in place. However the roles and responsibilities of the various institutions involved in the safety net are not always consistent with their objectives, powers, and mandates, while a well-specified strategy to preserve the stability of the system (e.g., with clear responsibilities for monitoring systemic risks and taking macro prudential decisions) and definition or formal measurement of systemic risk have not yet been established. Furthermore, coordination with foreign supervisors of international banks does not include designing contingency plans to address a possible cross-border event. This paper is divided into following four parts: part one is introduction; part two gives systemic liquidity management and emergency liquidity assistance; part three is bank resolution and deposit insurance; and part four gives crisis management arrangements.